2019
DOI: 10.3390/v11030275
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Filovirus-Resistant Cell Line SH-SY5Y Reveals Redundant Role of Cell Surface Entry Factors

Abstract: Filoviruses infect a wide range of cell types with the exception of lymphocytes. The intracellular proteins cathepsin B and L, two-pore channel 1 and 2, and bona fide receptor Niemann–Pick Disease C1 (NPC1) are essential for the endosomal phase of cell entry. However, earlier steps of filoviral infection remain poorly characterized. Numerous plasma membrane proteins have been implicated in attachment but it is still unclear which ones are sufficient for productive entry. To define a minimal set of host factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 78 publications
(127 reference statements)
1
8
0
Order By: Relevance
“…At MOI of 0.01, TIM-1 WT expression increased susceptibility by 12-fold whereas Axl WT expression resulted in a twofold increase (Figure 1B,C). Notably, TIM-1 WT and Axl WT expressing HEK293T cells were more susceptible to CHIKV (33-fold and 10-fold respectively) and Ebola virus (18-fold and five-fold respectively) glycoprotein-based lentiviral pseudoparticles demonstrating that the proteins are functional as previously reported [18,[67][68][69] (Supplementary Figure S2B). Next, we analyzed the susceptibility of the cells to authentic CHIKV at different hours post infection (hpi).…”
Section: Ectopic Tim-1 Expression Enhances Chikv Infection In Hek293t Cellssupporting
confidence: 79%
“…At MOI of 0.01, TIM-1 WT expression increased susceptibility by 12-fold whereas Axl WT expression resulted in a twofold increase (Figure 1B,C). Notably, TIM-1 WT and Axl WT expressing HEK293T cells were more susceptible to CHIKV (33-fold and 10-fold respectively) and Ebola virus (18-fold and five-fold respectively) glycoprotein-based lentiviral pseudoparticles demonstrating that the proteins are functional as previously reported [18,[67][68][69] (Supplementary Figure S2B). Next, we analyzed the susceptibility of the cells to authentic CHIKV at different hours post infection (hpi).…”
Section: Ectopic Tim-1 Expression Enhances Chikv Infection In Hek293t Cellssupporting
confidence: 79%
“…Initial EBOV attachment to the DC surface is mediated by several receptors that recognize different elements on the viral membrane and often have a redundant activity [105]. C-type lectin receptors (CLRs) such as the dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin (DC-SIGN) and the liver/lymph node sinusoidal endothelial C-type lectin (LSECtin) mediate viral attachment through binding to viral glycoproteins [106,107], while receptors of the TIM/TAM families (comprising the T cell immunoglobulin and mucin domain receptor along with Tyro-Axl-Mer receptors) recognize phosphatidylserine lipids present on the viral envelope [108] ( Figure 2B).…”
Section: The Role Of Siglec-1 In DC Infection and Antigen Presentationmentioning
confidence: 99%
“…In our study, we found that DIPL strongly correlates with both antiviral activity and with hydrophobicity. However, visible DIPL itself is not required for antiviral activity of CADs since effects like EBOV VLP inhibition (32) Filoviruses are late-penetrating viruses that are taken up into endosomes following low-specificity interactions with one or more of various cell surface attachment factors (34). Within the endosome, they undergo gp priming by low-pH dependent cathepsin and interact with their endolysosomal receptor NPC1, a cholesterol transporter (50).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were performed in the endothelium/lung-hybrid cell line EA.hy926 that is easy to cultivate and gives low background. Besides monocytes, macrophages, endothelial cells, hepatocytes and fibroblasts, this cell line was shown to be susceptible to several enveloped viruses including filoviruses(11,13,34,35). -3.7 µmol/L) and C max(sertraline) = 0.352 µmol/L, which can accumulate up to 20fold in the liver…”
mentioning
confidence: 99%